Exploration of assistive technology for uniform laparoscopic surgery. Issue 4 (19th February 2018) - Sato, Masakazu; Koizumi, Minako; Hino, Takahiro; Takahashi, Yu; Nagashima, Natsuki; Itaoka, Nao; Ueshima, Chiharu; Nakata, Maki; Hasumi, Yoko
Abstract: Introduction: Laparoscopic surgery is less invasive than open surgery and is now common in various medical fields. However, laparoscopic surgery is more difficult than open surgery and often requires additional time for the operator to achieve mastery. Therefore, we investigated the use of assistive technology for uniform laparoscopic surgery. Methods: We used the OpenCV2 library for augmented reality with an ArUco marker to detect and estimate forceps positioning. We used Sense HAT as the gyro sensor. The development platforms used were Mac OS X 10.11.3 and Raspberry Pi 3, model B. Results: By attaching the ArUco marker to the needle holder, we could draw a line vertically to the marker. When the needle was held, a cube could be imagined, and both the needle and lines could be used to determine the appropriate position. By attaching the gyro sensor to the camera, we could detect its angle of rotation. We obtained stabilized images by rotating the image by the detected degrees; this was possible for any camera position. Conclusions: Assistive technology allowed us to obtain consecutive converted images in real time and may be readily applicable to clinical practice.